Hirschsprung's disease prognosis: significance of the length of aganglionosis and reference value for the dilated segment resection length - Jia, Yingyu; Li, Bingliang; Xi, Hongwei; Ren, Hongxia (Frontiers in Pediatrics, 2025)
BackgroundThe appropriate length of resection for the dilated segment in Hirschsprung's disease (HSCR) remains a subject of debate, and the correlation between postoperative clinical outcomes has yet to be elucidated. This study aimed to explore the relationship between the dilated segment resection length (DSRL) and the short-term clinical outcome of HSCR, as well as to determine the optimal DSRL value.MethodsThe clinical data of all children with HSCR who underwent a pull-through surgery at Shanxi Children's Hospital from May 2016 to September 2023 were analyzed retrospectively, the baseline characteristics such as sex, gestational age, family history, and complications such as soiling, perianal erosion, constipation were collected. The groups were stratified in recto-sigmoid aganglionosis (short-segment) and extended colonic (long-segment), and DSRL was divided into three groups: DSRL < 10 cm, 10 ≤ DSRL < 20 cm, and DSRL ≥ 20 cm. The Wingspread score system was used to evaluate anal function and analyze the short-term clinical outcome.ResultsA total of 223 children were included in the study, among which 104 cases had short-segment HSCR and 119 cases had long-segment HSCR. The median age at which pull-through surgery was performed was 4 months. In cases of short-segment HSCR, aside from preoperative anemia, baseline characteristics showed no statistically significant differences among the three groups. No statistically significant association was observed between DSRL, the total length of intestinal resection, the length of aganglionosis,and postoperative clinical outcomes.For short-segment HSCR, the best postoperative bowel function was observed when DSRL < 10 cm, with the optimal value being 7.25 cm. In cases of long-segment HSCR, no statistically significant differences in baseline characteristics were observed among the three groups. DSRL, the total length of intestinal resection and the length of aganglionosis all showed statistically significant differences in relation to soiling and perianal erosion. For long-segment HSCR, the best postoperative bowel function was observed when 10 ≤ DSRL < 20 cm, with the optimal value being 13.00 cm.ConclusionsNot only the dilated segment resection length matters for the outcome but also the length of aganglionosis. For short-segment HSCR, DSRL, the total length of intestinal resection and the length of aganglionosis showed no significant impact on short-term clinical outcomes. In contrast, these parameters in long-segment HSCR were significantly associated with soiling and perianal erosion, although overall patient quality of life remained satisfactory. Data from a single clinical center suggest that optimal clinical outcomes for children are achieved when the DSRL measurements are 7.25 cm for short-segment HSCR and 13.00 cm for long-segment HSCR.